Prognostic value of 99mTc-ECD brain perfusion SPECT in patients with atrial fibrillation and dementia - Hidenobu Hashimoto; Rine Nakanishi; Sunao Mizumura; Yukiko Hashimoto; Yuriko Okamura; Kyoko Yamanaka; Takanori Ikeda (EJNMMI Research, 2020)
Abstract Background Patients with atrial fibrillation (AF) and dementia experience reduced quality of life and increased mortality. Technetium 99m ECD brain perfusion single-photon emission computed tomography (99mTc-ECD brain perfusion SPECT) is a beneficial modality for diagnosing dementia and identifying high-risk patients with mild cognitive impairment. The aim of this study was to evaluate the prognostic value of brain perfusion using 99mTc-ECD SPECT in patients with AF and dementia. Methods Of a total of 405 consecutive patients diagnosed with AF as cardiac outpatients with dementia using the Mini-Mental State Examination by neurologists or psychiatrists, we identified 170 patients (81 ± 10 years) who underwent 99mTc-ECD brain perfusion SPECT. Of them, 73, 73, and 24 were diagnosed with Alzheimer’s dementia (AD), vascular dementia (VD), and non-specified dementia, respectively. A multivariable Cox model was used to assess if higher Z-score by 99mTc-ECD brain perfusion SPECT and clinical parameters were associated with major adverse cardiovascular events (MACE) including cardiac death, myocardial infarction, hospitalization for heart failure, and stroke. Results During a mean follow-up of 1258 ± 1044 days, 62 MACE occurred. There was no significant difference in MACE between AD and VD (33%, vs. 44%, p = 0.153). The multivariable Cox model confirmed that the higher Z-score of temporo-parieto-occipital lobe was associated with increased MACE compared to the lower group (HR 2.521, 95% CI 1.465–4.337, p < 0.001). Conclusion This study demonstrated that decreased cerebral blood flow in the temporo-parieto-occipital lobe could be a potential prognostic value in patients with both AF and dementia.